Dava Şartı Olarak Arabuluculuk Hükümlerinin Sendikalar ve Toplu İş Sözleşmesi Kanunu Açısından Uygulanması - (:unkn) unknown (My University, 2019)
7036 sayılı İş Mahkemeleri Kanunu ile Türk İş Hukuku uygulamasında yeni bir dönem başlamış ve iş sözleşmesi taraflarının kanuna, bireysel veya toplu iş sözleşmesine dayanan alacak, tazminat ve işe iade talepleri hususunda dava açmadan önce arabuluculuk yoluna başvurmaları bir dava şartı olarak öngörülmüştür. Tarafların arabuluculuğa başvurmak zorunda oldukları alacak, tazminat veya işe iade taleplerine dayanak olabilecek kanunlardan biri de 6356 sayılı Sendikalar ve Toplu İş Sözleşmesi Kanunudur. 6356 sayılı Kanunda bu Kanunun uygulanmasından doğan uyuşmazlıkların iş davalarına bakmakla görevli mahkemelerde görüleceği düzenlenmiştir. Çalışmamızda iş mahkemesinde görülen 6356 sayılı Kanuna ilişkin hangi uyuşmazlıklarda arabuluculuğun dava şartı olduğu incelenmiştir.

The Employment Courts Code numbered 7036 opened a new era in the Turkish Employment Law by introducing mandatory mediation for all the claims concerning the receivables and compensa?tions of the parties of the employment agreements as well as reinstatement to the work, arising from codes, individual employment agreements and col?lective bargaining agreements. Due to mediation is regulated as a cause of action in the Code no. 7036, these claims cannot be brought up to the court level unless the mediation process has been con?sumed. The Code on Trade Unions and Collective Labour Agreements numbered 6356 is one of the codes, which such claims may arise from. Moreover, the Code no. 6356 regulates that the disputes aris?ing from the application of this Code are resolved by the courts which has jurisdiction over the em?ployment cases. In this article, it is discussed for which disputes concerning the Code no. 6356 me?diation is a cause of action.
Application of the Provisions About Mediation As A Cause of Action For the Code on Trade Unions and Collective Labour Agreements